2017
DOI: 10.1371/journal.pone.0177182
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-related microRNA expression level in the bovine milk is affected by mastitis

Abstract: MicroRNA (miRNA) in tissue and liquid samples have been shown to be associated with many diseases including inflammation. We aimed to identify inflammation-related miRNA expression level in the bovine mastitis milk. Expression level of inflammation-related miRNA in milk from mastitis-affected and normal cows was analyzed using qPCR. We found that expression level of miR-21, miR-146a, miR-155, miR-222, and miR-383 was significantly upregulated in California mastitis test positive (CMT+) milk. We further analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 57 publications
3
46
0
Order By: Relevance
“…Second, this population did not include subjects with nonmalignant mammary pathology such as mastitis or benign mammary tumors. This could be relevant as research evaluating miRNA in cow and porcine milk has identified particular miRNA signature that increase with mastitis, including miR‐21, miR‐146a, miR‐155, miR‐222, and miR‐383 26 . Fortunately, these miRNAs are not among the most relevant potential biomarkers identified in this dataset.…”
Section: Discussionmentioning
confidence: 93%
“…Second, this population did not include subjects with nonmalignant mammary pathology such as mastitis or benign mammary tumors. This could be relevant as research evaluating miRNA in cow and porcine milk has identified particular miRNA signature that increase with mastitis, including miR‐21, miR‐146a, miR‐155, miR‐222, and miR‐383 26 . Fortunately, these miRNAs are not among the most relevant potential biomarkers identified in this dataset.…”
Section: Discussionmentioning
confidence: 93%
“…Milk microRNAs are of particular importance because of their potential use as diagnostic, prognostic and functional tools in disease assessment and management (Alsaweed, Lai, Hartmann, Geddes, & Kakulas, ; Cui et al., ; Decmann et al., ; Iannaccone et al., ; Lai et al., , ; Markkandan et al., ; Melnik & Schmitz, ; Perge, Nagy, Decmann, Igaz, & Igaz, ; Schanzenbach, Kirchner, Ulbrich, & Pfaffl, ; Tome‐Carneiro et al., ). It is also of interest to study their impact in infant development in the context of infant formulas, which are poor in microRNAs (Alsaweed et al., ; Chen et al., ; Oh, Park, Son, & Kim, ), for newborns not fed with maternal milk (Oh et al., ; Zempleni et al., 2016).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…In milk, microRNA expression was related to mammary gland conditions, including infections (Iannaccone et al., ; Lai et al., , ; Sun et al., ), cancer (Decmann et al., ; Do Canto et al., ; Hesari et al., ), pregnancy and lactation status (Carney et al., ; Perri et al., ; Schanzenbach et al., ), and maternal diet (Chen et al., ). Therefore microRNAs in milk were studied for their potential as biomarkers (Gustafson, Tyryshkin, & Renwick, ; Melnik & Schmitz, ) such as quality controls of commercial milk (Oh et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…miR‐21, miR‐146a, and miR‐155 are well‐studied miRNAs implicated in the immune responses initiated by the Toll‐like receptor signal transduction pathways, and regulate the activation of the transcription factor nuclear factor kappa B (NF‐κB) . In our previous study, we demonstrated that these inflammation‐related miRNAs are affected by mastitis and that the miRNAs in milk have potential utility as biomarkers of bovine mastitis .…”
Section: Introductionmentioning
confidence: 99%